Nieuwe eenvoud en high tech : van Villa M tot het Fotomuseum - Boone, Veronique; Strauven, Francis, 1942- (Tielt : Lannoo, 2008)
Kerksken, Wandre, Zedelgem, Meise, Brussel, Antwerpen, Dilbeek, Hasselt, Brasschaat, Dworp, Gent, Wemmel, Baardegem, Luik, Marche, Antwerpen, Sint-Ankelinks, Eeklo, Zoersel, Dendermonde, Aalst, Hornu, Kortrijk, Maaseik, Machelen-a -d -Leie, Oudenaarde, Scherpenheuvel, Bonheiden, Namen, Sint-Niklaas, Nijvel, GIts, Heusy, Sint-Pietes-Woluwe
Keywords: Architectuur -- België